ANALISIS ASPEK LITERASI SAINS PADA BUKU TEKS PELAJARAN IPA KELAS V SD - Nurfaidah, Siti Sholiha (Universitas Pendidikan Indonesia, 2017)
The ability of scientific literacy important to have learners in understanding the environment, economy and problems in modern society. One effort to improve science literacy through the analysis of textbooks. This research analyzes aspects of scientific literacy in the fifth grade elementary science textbooks. Aspects of scientific literacy are analyzed include science as a way of thinking and the interaction of science, technology society. This type of research is descriptive, to collect data in the form of documentation. One book as a whole has been analyzed and generate different presentation of scientific literacy, namely:Â 5.8% (aspects of science as a way of thinking) and 1.2% (aspects of the interaction of science, technology and society). The second aspect is still slightly presented in each chapter. Even aspects of the interaction of science, technology and society only appears in Chapter 7 (7.4%) and Chapter 4 (0.5%). The following findings indicate that this book does not emphasize material support on the acquisition process and context.Keywords: science literacy; way of thinking; the interaction of science, technology and society; analysis of textbooks.